MRI in Leber's hereditary optic neuropathy: the relationship to multiple sclerosis. Issue 5 (22nd July 2014) - Matthews, Lucy; Enzinger, Christian; Fazekas, Franz; Rovira, Alex; Ciccarelli, Olga; Dotti, Maria Teresa; Filippi, Massimo; Frederiksen, Jette L; Giorgio, Antonio; Küker, Wilhelm; Lukas, Carsten; Rocca, Maria A; et al.
Abstract : Background: Leber's hereditary optic neuropathy (LHON) and a multiple sclerosis (MS)-like illness appear to coexist 50 times more frequently than would be expected by chance. This association of LHON and MS (LMS) raises an important question about whether there could be a common pathophysiological mechanism involving mitochondrial dysfunction. Objective: The primary aim was to define MRI features of LMS and LHON, and to assess the proportions of individuals displaying features typical of MS. Secondarily, we investigated the effect of gender on the risk of developing white matter lesions in the context of LHON. Methods: A blinded standardised review of conventional brain MRIs of 30 patients with MS, 31 patients with LHON and 11 patients with LMS was conducted by three independent experts in the field. MS-like MRI features were assessed. Results: All patients with LMS and 26% of patients with LHON had white matter lesions. Of these, all patients with LMS and 25% with LHON were found to have an MRI appearance typical of MS. Female patients with LHON had a significantly greater risk of having white matter lesions consistent with MS compared with male patients (relative risk 8.3). Conclusions: A blinded review of conventional brain MRIs shows that patients with LMS have a scan appearance indistinguishable from MS. Mitochondrial dysfunction could be a common pathophysiological pathway in the formation of white matter lesions. There appears to be a strong female influence on the radiological appearance as well as clinical development of MS in patients with LHON.